Detection of the ST111 Global High-Risk Pseudomonas aeruginosa Clone in a Subway Underpass - Balázs Libisch; Chioma Lilian Ozoaduche; Tibor Keresztény; Anniek Bus; Tommy Van Limbergen; Katalin Posta; Ferenc Olasz (Current Issues in Molecular Biology)
P. aeruginosa strain NL201 was cultured from an urban water drain in a populated subway underpass as an environmental isolate for the ST111 global high-risk P. aeruginosa clone. In addition to carrying generally present intrinsic P. aeruginosa antibiotic resistance genes, this serotype O4 isolate also carries a set of additional acquired resistance determinants, including aadA2, blaOXA-10, sul1, and an aac(6′)-Ib family gene. The NL201 isolate features the blaPDC-3 allele, which was found to confer significantly higher catalytic efficiency against cefepime and imipenem compared to blaPDC-1, as well as the potent P. aeruginosa virulence factors exoS, exoT, and algD. Serotype O4 isolates of the ST111 global high-risk P. aeruginosa clone have been reported from clinical samples in Canada and the USA, human stool samples in France, and environmental samples (such as cosmetic, hospital drains, and urban water drain) from various European countries. These observations underscore the effective dissemination of the ST111 global high-risk P. aeruginosa clone between different hosts, environments, and habitats, and they warrant targeted investigations from a One Health perspective on the possible routes of its spread and molecular evolution.